Employee Performance Model: Implementation of Work Environment Work Discipline and Competence - Lokot Muda Harahap (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This research was conducted on employees of Bank Bukopin's Setia Budi Medan Branch Office in the staffing section with a population of 106 employees. The sampling technique used purposive sampling method and the research sample obtained was 42 respondents. The method used is a quantitative research method. This study uses instrument tests (validity test and reliability test), data analysis techniques (classical assumption test: multicollinearity test, heteroscedasticity test, and normality test), multiple linear regression test, Coefficient of Determination test (D), hypothesis test (partial t test and simultaneous f test). Meanwhile, for data processing using SPSS for Windows Realease 21.0 program. Based on the results of this study, the work discipline variable is a variable that has a dominant influence on employee performance variables at Bank Bukopin employees at the Setia Budi Branch Office (KCP). It is proven by the results of the t-test that the variables of work environment, work discipline, and compensation have a significant effect on employee performance. The results of the statistical t-test of the work environment variables t arithmetic > t table are: (3.120 > 2.024), the work discipline variable is: (2.306 > 2.024), while the compensation variable has a value (4.181 > 2.024). The results of the F test can be concluded that there is a simultaneous and significant effect between the variables of work environment, work discipline, and compensation on employee performance. The result of the calculated F test is greater than the F table value (58.449 > 4, 066) with a probability less than 0.05 (0.000 < 0.05). The results obtained by the coefficient of determination or (R2) of 0.808. This means that 80.8% of the variation of changes in employee performance ups and downs is due to changes in work environment variables, work discipline, compensation. While the remaining 19.2% was caused by other factors that were not analyzed in the model used in the study.